What’s Love Got to Do with It?: Thinking about Democracy in Early Childhood Curriculum with Hannah Arendt - Nilsson, Jenni (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2025)
This paper explores how Hannah Arendt’s view of education as love (1958) can contribute to refreshed perspectives of democratic education. In recent decades, the task of contemporary early childhood education has gradually moved towards an enhanced focus on individual learning and freedom of choice, closely intertwined with an image of the child as an active participant with rights (e.g., Kjørholt, 2012; Sjöstrand Öhrfelt, 2019). The increased emphasis on subject knowledge, measurable achievements, and competition, mainly driven by a neoliberal agenda, is seen to affect and possibly reduce the role of care and democracy within education (e.g., Brogaard Clausen, 2015; Moss, 2017). Arendt’s views on education as love offer a thought-provoking mirror to the changed landscapes of early childhood education. She was critical of the emancipation of children and claimed that, as newcomers, children need to be protected from the world, as well as the world also needing to be protected from the children. Through a theoretical conversation between Arendt and Joan Tronto’s theory of democratic care (2015), I will argue that interdependency and vulnerability need to be acknowledged within contemporary democratic early childhood education, and that allocation of responsibility continues to be an essential issue within education.